Long term storage of Podospora anserina - O. BEGEL; L. BELCOUR (Fungal Genetics Reports, 1991)
Until now, maintenance of Podospora anserina strains was tedious, requiring yearly sexual crosses, spore isolation and germination, verification of the genotype and transfer of mycelium to stock tubes maintained at 4 C. We have circumvented these difficulties by storage of ascospores at -80 C.